Developmental pathways from child maltreatment to adolescent marijuana dependence: Examining moderation by FKBP5 - Handley, Elizabeth D. (Dev Psychopathol, 2015)
The current study examined the prospective association between child maltreatment and the development of substance use disorder (SUD) in adolescence with the aim of investigating pathways underlying this relation, as well as genetic moderation of these developmental mechanisms. Specifically, we tested whether youth who experienced maltreatment prior to age 8 were at risk for the development of marijuana dependence in adolescence by way of a childhood externalizing pathway and a childhood internalizing pathway. Moreover, we tested whether variation in FKBP5 CATT haplotype moderated these pathways. The participants were 326 children (n=179 maltreated; n=147 nonmaltreated) assessed across two waves of data collection (childhood: ages 7–9 and adolescence: ages 15–18). Results indicated that higher levels of child externalizing symptoms significantly mediated the effect of child maltreatment on adolescent marijuana dependence symptoms for individuals with 1–2 copies of the FKBP5 CATT haplotype only. We did not find support for an internalizing pathway from child maltreatment to adolescent marijuana dependence, nor did we find evidence of moderation of the internalizing pathway by FKBP5 haplotype variation. Findings extend previous research by demonstrating that whether a maltreated child will traverse an externalizing pathway toward SUD in adolescence is dependent on FKBP5 genetic variation.